Causes and predictors of 30‐day readmission after cardiovascular implantable electronic devices implantation: Insights from Nationwide Readmissions Database. (20th December 2017) - Ahmad, Shahzad; Munir, Muhammad Bilal; Sharbaugh, Michael S.; Althouse, Andrew D.; Pasupula, Deepak Kumar; Saba, Samir
Abstract: Introduction: Readmissions are a burden on health care resources and have negative impact on patients. Cardiovascular implantable electronic devices (CIEDs) are frequently used in the management of rhythm disorders and advanced heart failure. We assessed 30‐day readmissions in patients admitted for CIED implantation in a sample of United States patients. Methods: Data were extracted from Nationwide Readmissions Database for calendar year 2013. Patients admitted for CIED implantation were identified using ICD‐9 codes. Patients <18 years of age, with missing data, who died during hospitalization or discharged in December were excluded. Primary endpoint was all‐cause 30‐day readmission rate. Factors associated with 30‐day readmissions were identified and examined using multivariate logistic regression. Results: We identified 320, 783 admissions for CIED implantations. After applying exclusion criteria, 290, 420 patients were included in final analysis, out of whom 45, 467 (15.7%) patients were readmitted within 30 days. Readmitted patients were younger and had more comorbidities. Septicemia (5.1%), pneumonia (3.4%), CHF (2.35%), and paroxysmal ventricular tachycardia (2.3%) were common primary causes of 30‐day readmission. Young age, female gender, key comorbidities, weekend admissions, and admission to medium and large size hospital were independent predictors of 30‐day readmissions. Conclusion: In our study, 15.7% patients were readmitted within 30 days of an index admission for CIED implantation. Most readmissions were due to infectious or cardiovascular causes. There is a need to identify patients at risk for readmission to improve outcomes and curb the cost of care.